Portables, luggables, and transportables: Historicizing the imagined affordances of mobile computing. (September 2019) - Alper, Meryl
This article contributes to the history of "mobile media beyond mobile phones" by accounting for genres of portable computing (or "portables") that emerged in the late 1980s. Though largely overlooked by historians of technology, these mobile, less-than-mobile, and relatively immobile devices helped shape the social and cultural uses of contemporary mobile communication. I argue that the technological capabilities of portables altered users' expectations for how and where computers could be incorporated into daily life, be it near bodies, on hand, or at one's fingertips. While the market for bulky portables dwindled by the late 1990s, as laptops and cell phones became more ubiquitous, these consumer electronics are nonetheless useful today for understanding the perpetual role of materiality and embodiment in how we conceive of the imagined affordances of mobile communication technologies.